2017
DOI: 10.1016/j.cellimm.2017.09.004
|View full text |Cite
|
Sign up to set email alerts
|

Signals that drive T-bet expression in B cells

Abstract: Transcription factors regulate various developmental and functional aspects of B cells. T-bet is a recently appreciated transcription factor associated with “Age-associated B cells” or ABCs, the development of autoimmunity, and viral infections. T-bet expression is favored by nucleic acid-containing antigens and immune complexes and is regulated by interplay between various cytokines, notably, the TFH cytokines IL-21, IL-4 and IFNγ. Adaptive signals by themselves cannot upregulate T-bet; however, they have a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
43
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 41 publications
(44 citation statements)
references
References 37 publications
1
43
0
Order By: Relevance
“…Contrasting with FO and MZ B cells, ABCs do not depend on BAFF for survival; however, they express BAFFR/BR3 and TACI receptors for this cytokine . Furthermore, and unlike these 2 mentioned lineages, they are not the product of B lymphopoiesis in the aged microenvironment, nor do they seem to be self‐renewing . Then, it seems that the origin of these lymphocytes can be traced to exhaustive‐expanded FO B cells …”
Section: Age‐associated B Cellsmentioning
confidence: 99%
See 2 more Smart Citations
“…Contrasting with FO and MZ B cells, ABCs do not depend on BAFF for survival; however, they express BAFFR/BR3 and TACI receptors for this cytokine . Furthermore, and unlike these 2 mentioned lineages, they are not the product of B lymphopoiesis in the aged microenvironment, nor do they seem to be self‐renewing . Then, it seems that the origin of these lymphocytes can be traced to exhaustive‐expanded FO B cells …”
Section: Age‐associated B Cellsmentioning
confidence: 99%
“…100 Furthermore, and unlike these 2 mentioned lineages, they are not the product of B lymphopoiesis in the aged microenvironment, nor do they seem to be self-renewing. 103,104 Then, it seems that the origin of these lymphocytes can be traced to exhaustive-expanded FO B cells. 105 Regarding the necessary elements that are involved in ABCs generation besides T-bet, the initial characterization of this B cell subset demonstrated that TLR7, TLR9, and MyD88, but not IFN-R, are required for the accumulation of these cells.…”
Section: Age-associated B Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…Within these, further phenotypic and functional categories exist; for example, phenotypically defined T cell subsets differ in anatomic location, cytokine profiles, and the key transcriptional regulators that control these features. [21][22][23][24][25][26] These T-bet + B cells have been identified in both mice and humans in a variety of contexts, including aging, [27][28][29] autoimmunity, 28,[30][31][32][33][34] and infection. Thus, Bmem with distinct phenotypic and functional abilities have been described by several groups, [11][12][13][14][15][16] and PC pools with profoundly different turnover rates are now appreciated.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, different mature pre-immune lymphocyte subsets such as transitional (TR), follicular (FO), marginal zone (MZ), and B1 B cells have characteristic anatomic distributions and play distinct roles in primary immune responses. [21][22][23][24][25][26] These T-bet + B cells have been identified in both mice and humans in a variety of contexts, including aging, [27][28][29] autoimmunity, 28,30-34 and infection. Within these, further phenotypic and functional categories exist; for example, phenotypically defined T cell subsets differ in anatomic location, cytokine profiles, and the key transcriptional regulators that control these features.…”
mentioning
confidence: 99%